Cognitive functioning in sporadic amyotrophic lateral sclerosis: a six month longitudinal study. Issue 5 (13th April 2006) - Robinson, K M; Lacey, S C; Grugan, P; Glosser, G; Grossman, M; McCluskey, L F
Abstract : Objective: To observe changes in cognition over six months in subjects with recently diagnosed sporadic amyotrophic lateral sclerosis (ALS). Methods: The study used a between-group and within-group longitudinal design. Nineteen ALS subjects and eight matched caregivers were recruited to participate in baseline neuropsychological assessments that were repeated six months later. Between group comparisons for these variables were undertaken at baseline and six months later. Within group/across time comparisons for these variables were carried out for both groups. Individual analyses for the neuropsychological variables using z scores were done for the ALS subjects using their baseline performance as the basis for comparison with their six month performance. Results: The between-group and within-group comparisons did not show significant differences in cognitive function over time. In individual analyses, however, seven of 19 ALS subjects (36.84%) developed abnormal neuropsychological performance over six months. Conclusions: Early in the disease course, over one third of the ALS subjects developed cognitive deficits over six months. These findings support the hypothesis that cognitive deficits in ALS become more prominent over time.